Denoising and Voxelization for Finite Element Analysis: A Review - Sara Gonizzi Barsanti (Engineering Proceedings)
The conservation of cultural heritage is fundamental, and it is difficult to predict how heritage objects will relate with structural damages. For these objects, the most used process for the analyses involves NURBS models that may introduce an excessive level of approximation leading to wrong simulation results. This work presents the preliminary review of literature and first tests regarding denoising and voxel algorithms and their application for the creation of volumetric models of a reconstruction of an ancient scorpionide, to identify the bottlenecks of the post-processing method for the creation of volumetric data for the FEA of cultural heritage.